Acute Pericarditis Leading to a Diagnosis of SLE: A Case Series of 3 Patients. (March 2022) - Narang, Vishal K.; Bowen, Jonathan; Masarweh, Omar; Burnette, Shane; Valdez, Michael; Moosavi, Leila; Joolhar, Fowrooz; Win, Theingi Tiffany
In systemic lupus erythematosus (SLE), cardiac manifestations are known to be present in up to 50% of patients. However, it is rare for acute pericarditis to be the leading symptom at the time of diagnosis of SLE occurring in up to 1% of patients. We present a case series in which 3 patients with no prior history of SLE presented with acute pericarditis. This was found to be the leading manifestation of their disease, which ultimately led to the diagnosis of SLE. These patients were initially treated with nonsteroidal anti-inflammatory drugs and colchicines; however, steroids and disease-modifying anti-rheumatologic agents were ultimately added to their medical therapy.